2015
DOI: 10.17533/udea.iatreia.v29n1a04
|View full text |Cite
|
Sign up to set email alerts
|

Representaciones sociales sobre el cuerpo en estudiantes de Medicina, Medellín, 2014

Abstract: RESUMENIntroducción: los discursos filosóficos y socioantropológicos sobre el cuerpo no han sido objeto de interés en la formación médica.Objetivo: caracterizar las representaciones sociales del cuerpo en estudiantes de Medicina, Medellín, 2014.Métodos: etnografía con 11 estudiantes seleccionados mediante muestreo teórico. Las representaciones sociales se estudiaron desde el enfoque procesual. Se aplicaron los criterios de rigor metodológico de credibilidad, auditabilidad y transferibilidad.Resultado: se descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…This is interesting because epistemologically, the notion of the mind has been used to contrast it with the body; this notion relates to a very old philosophical problem: the mind-body dualism elaborated by Descartes. This finding coincides with a study on social representations of the body in medical students in Medellín, where the authors found that the body-mind division is also strongly ingrained in the conceptions of the interviewed students [28]. The convergence of these results serves as a good example of what Ian Hacking [29] and Lorraine Daston [30] understand as applied metaphysics; that is, how old philosophical ideas "seep" into everyday life or professional life, determining and guiding people's actions.…”
Section: Discussionsupporting
confidence: 90%
“…This is interesting because epistemologically, the notion of the mind has been used to contrast it with the body; this notion relates to a very old philosophical problem: the mind-body dualism elaborated by Descartes. This finding coincides with a study on social representations of the body in medical students in Medellín, where the authors found that the body-mind division is also strongly ingrained in the conceptions of the interviewed students [28]. The convergence of these results serves as a good example of what Ian Hacking [29] and Lorraine Daston [30] understand as applied metaphysics; that is, how old philosophical ideas "seep" into everyday life or professional life, determining and guiding people's actions.…”
Section: Discussionsupporting
confidence: 90%
“…These notions may be showing a change from an individualistic social order, in which the body of others and their care is the responsibility of each other. 29 One achievement of the educational process was a change of the traditional conceptions of oral health education-a change corroborated by other studies which have recognized the importance of overcoming the traditional approach of information-based health education and a behavioral change, subsidiary of the biomedical model-. 30 Hence the importance of adopting broad approaches linked to the conception of self-care and caring for others with love, as a possibility to produce healthy practices.…”
Section: Discussionmentioning
confidence: 77%